Essential Oils Can Mitigate Adverse Effects of Prolonged Masking in the Hospital Setting. Issue 6 (November 2022) - Patterson, Jan E.; Kendrick, Rebekah; Salazar, Camerino I.; Vera, Ana; MacNaughton, Michael G.; Reed, Charles
Abstract : Adverse symptoms of prolonged masking were reported by personnel. A drop of essential oil was added to the mask to mitigate these effects and significantly lessened symptoms. Symptoms declined by almost half, including anxiety, nausea, and indigestion. This simple intervention can mitigate adverse effects of prolonged masking in the hospital setting.